Case report: A novel pathogenic FRMD7 variant in a Turner syndrome patient with familial idiopathic infantile nystagmus - Hafdaoui, Sara; Ciaccio, Claudia; Castellotti, Barbara; Sciacca, Francesca L.; Pantaleoni, Chiara; D'Arrigo, Stefano (Frontiers in Neurology, 2023)
Infantile idiopathic nystagmus (IIN) is an oculomotor disorder characterized by involuntary bilateral, periodic ocular oscillations, predominantly on the horizontal axis. X-linked IIN (XLIIN) is the most common form of congenital nystagmus, and the FERM domain-containing gene (FRMD7) is the most common cause of pathogenesis, followed by mutations in GPR143. To date, more than 60 pathogenic FRMD7 variants have been identified, and the physiopathological pathways leading to the disease are not yet completely understood. FRMD7-associated nystagmus usually affects male patients, while it shows incomplete penetrance in female patients, who are mostly asymptomatic but sometimes present with mild ocular oscillations or, occasionally, with clear nystagmus. Here we report the first case of a patient with Turner syndrome and INN in an XLIIN pedigree, in which we identified a novel frameshift mutation (c.1492dupT) in the FRMD7 gene: the absence of one X chromosome in the patient unmasked the presence of the familial genetic nystagmus.